Integrating Gayo Tradition: Alang Tulung in Blended Project-Based Learning - Lisa Lisa; E. Elvis Napitupulu; Asmin Panjaitan; Edi Syahputra; Elmanani Simamora (AL-ISHLAH: Jurnal Pendidikan, 2025)
In the context of globalization, traditional cultural values are increasingly at risk of being overlooked in modern education. The Alang Tulung tradition of the Gayo people in Aceh, which promotes gotong royong (mutual cooperation), social responsibility, and collaboration, offers meaningful values for character development in youth. This study investigates the integration of Alang Tulung into a Blended Project-Based Learning (BPjBL) model. A qualitative approach was employed, utilizing semi-structured interviews, classroom observations, learning outcome evaluations, and student surveys. The study aimed to assess both the cultural significance and educational effectiveness of the Alang Tulung-based BPjBL model. The findings indicate that incorporating Alang Tulung values into BPjBL enriched students’ learning experiences and supported cultural preservation. Academic performance improved significantly, with an N-Gain score of 0.72. Collaboration skills also increased, with an average score of 4.6 and 92% of students displaying optimal teamwork. Additionally, 90% of participants reported a deeper understanding of the Alang Tulung tradition, and 88% recognized its relevance to contemporary education. While the model proved effective, challenges such as limited internet connectivity and the absence of structured cultural learning modules were noted. These barriers suggest the need for infrastructure improvements and curriculum development. The integration of local cultural traditions like Alang Tulung into educational models can enhance student engagement, foster character development, and contribute to cultural preservation amidst globalization.